143k views
5 votes
What is (9x+5)-(4x+3)​

User Maelgrove
by
6.4k points

2 Answers

6 votes

Answer:

5x + 2

Explanation:

9x+5−(4x+3)

Distribute the negative sign

=9x+5+−1(4x+3)

=9x+5+−1(4x)+(−1)(3)

=9x+5+−4x+−3

Combine like terms

=9x+5+−4x+−3

=(9x+−4x)+(5+−3)

=5x+2

User Jeninne
by
6.1k points
5 votes

[ Answer ]


\boxed{5x \ + \ 2}

[ Explanation ]

(9x + 5) - (4x + 3)

Remove Parenthesis

9x + 5 - (4x + 3)

-(4x + 3): -4x - 3

9x + 5 - 4x - 3

[Simplify] 9x + 5 - 4x - 3: 5x + 2

5x + 2


\boxed{[ \ Eclipsed \ ]}

User Twil
by
6.8k points